CULTURAL TOURISM IN GJIROKASTRA - Kotollaku, Mimoza; Margariti, Magdalena (European Scientific Journal, ESJ, 2015)
Cultural tourism is gaining a great importance in the modern tourism industry, and it also represents an important and attractive power for local and international tourists. This allows destinations and regions to expand their customer basis, winning in this way new clients interested in different types of attractions and diversifying their offer, especially in cases of destinations which have no tourism typology (such as coastal and lake tourism), and cases which are required out of the tourism season, reducing in this way seasonality and having all year round tourism. In this paper our study refers to the valuable assets of Gjirokastra city, as part of the World Heritage Tourism, which are rich, diverse and scattered throughout the prefecture. In the recent years there has been a rapid growth in the foreign and local tourists visiting this country and playing an important role in the development of tourism and the incomes of this prefecture. According to the official data of Gjirokastra Municipality in 2009 the number of visitors was 15894 while in 2014 it reached 35000. The main purpose of this paper is to analyze the characteristics of cultural tourism, of heritage and events, and the theoretical background of the relationships between the concepts of tourism, culture, heritage, and events by analyzing their impact in these destinations closely related to the management, marketing, and the economic impact, of the involved and interested parties and their relationship with the local development. The methodology is based on a descriptive analysis based on the data obtained from a survey conducted to 300 tourists who visited Gjirokastra in 2013-2014 through a self-administered questionnaire. We are also referring to a study which was done by Gjirokastra Municipality in 2011. This study has identified the origins of the tourists visiting this place, the reasons for the visit and their touristic expenses. It also treats a number of problems, determining in this way the necessary conditions to introduce these cultural destinations to the tourism market. Finally the paper is concluded with some recommendations and conclusions for tourism stakeholders in the country. It is important to identify relevant strategies for cultural tourism through cooperation between government bodies and the private sector as an important factor for the promotion of Gjirokastra city as a tourist destination for local and foreign tourists.